Intracellular immunization against HIV infection with an intracellular antibody that mimics HIV integrase binding to the cellular LEDGF protein. Issue 1 (December 2017) - Bao, Leyuan; Hannon, Clare; Cruz-Mignoni, Abimael; Ptchelkine, Denis; Sun, Mei-yi; Miller, Ami; Bunjobpol, Wilawan; Quevedo, Camilo; Derveni, Mariliza; Chambers, Jennifer; Simmons, Alison; Phillips, Simon; et al.
Abstract Preventing the protein-protein interaction of the cellular chromatin binding protein Lens Epithelium-Derived Growth Factor (LEDGF) and human immunodeficiency virus (HIV) integrase is an important possible strategy for anti-viral treatment for AIDS. We have used Intracellular Antibody Capture technology to isolate a single VH antibody domain that binds to LEDGF. The crystal structure of the LEDGF-VH complex reveals that the single domain antibody mimics the effect of binding of HIV integrase to LEDGF which is crucial for HIV propagation. CD4-expressing T cell lines were constructed to constitutively express the LEDGF-binding VH and these cells showed interference with HIV viral replication, assayed by virus capsid protein p24 production. Therefore, pre-conditioning cells to express antibody fragments confers effective intracellular immunization for preventing chronic viral replication and can be a way to prevent HIV spread in infected patients. This raises the prospect that intracellular immunization strategies that focus on cellular components of viral integrase protein interactions can be used to combat the problems associated with latent HIV virus re-emergence in patients. New genome editing development, such as using CRISPR/cas9, offer the prospect intracellularly immunized T cells in HIV+ patients.